Pemodelan Gedung Kampus Universitas Muhammadiyah Sidoarjo dengan Metode Augmented Reality Sebagai Media Informasi - Utama, Bagas Riski; Rosid, Mochamad Alfan; Hindarto, Hindarto (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The purpose of making the UMSIDA Augmented Reality application is as an information medium as well as a promotional medium for prospective new students to introduce the campus during the promotion. The Augmented Reality visualization of the campus 1, campus 2 and campus 3 buildings at Muhammadiyah University of Sidoarjo can combine real and virtual objects in the form of 3-dimensional buildings in real time using the Marker Based Tracking method. This method produces an application that can display the building's visuals in 3 dimensions by scanning the markers on the brochure by directing the Android smartphone camera from various angles.